Kidney disease and risk of venous thromboembolism: a nationwide population‐based case‐control study. (29th July 2014) - Christiansen, C. F.; Schmidt, M.; Lamberg, A. L.; Horváth‐Puhó, E.; Baron, J. A.; Jespersen, B.; Sørensen, H. T.
Summary Background Chronic kidney disease is associated with hemostatic derangements, including both procoagulant activity and platelet dysfunction, which may influence the risk of venous thromboembolism. However, data associating kidney disease with risk of venous thromboembolism are sparse. Objectives We examined whether kidney disease is associated with increased risk of venous thromboembolism. Methods We conducted this nationwide case‐control study using data from medical databases. We included 128 096 patients with a hospital diagnosis of VTE in Denmark between 1980 and 2010 (54 473 had pulmonary embolism and 73 623 had deep venous thrombosis only) and 642 426 age‐ and gender‐matched population controls based on risk‐set sampling. We identified all previous hospital diagnoses of kidney disease, including nephrotic syndrome, glomerulonephritis without nephrotic syndrome, hypertensive nephropathy, chronic pyelonephritis/interstitial nephritis, polycystic kidney disease, diabetic nephropathy, or other kidney diseases. We used conditional logistic regression models to compute odds ratios (ORs) for venous thromboembolism with adjustment for potential confounders. Results Kidney disease was associated with an adjusted OR for venous thromboembolism ranging from 1.41 (95% CI, 1.22–1.63) for hypertensive nephropathy to 2.89 (95% CI, 2.26–3.69) for patients with nephrotic syndrome. The association was strongest within the first 3 months after a diagnosis of chronic kidney disease (adjusted OR for nephrotic syndrome = 23.23; 95% CI, 8.58–62.89), gradually declining thereafter. The risk, however, remained elevated for more than 5 years, especially in patients with nephrotic syndrome and glomerulonephritis. Conclusions Kidney diseases, in particular nephrotic syndrome and glomerulonephritis, were associated with an increased risk of venous thromboembolism.